PENGGUNAAN MEDIA PUZZLE DALAM MENINGKATKAN KEMAMPUAN MENULIS PARAGRAF DESKRIPSI PADA SISWA KELAS IV SD MUHAMMADIYAH 10 TALLO: penelitian tindakan kelas - Amiruddin, Haryanti Nurasmi; Muhammad Akhir; Haslinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' ability in writing descriptive paragraphs through the use of puzzle media. The research was conducted using Classroom Action Research (CAR) consisting of two cycles, each including planning, action, observation, and reflection stages. The subjects of this study were 20 fourth-grade students of SD Muhammadiyah 10 Tallo. Data were collected through observation, tests, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The results showed that the use of puzzle media significantly improved students' writing skills. In Cycle I, the average score reached 80 with 70% completeness, while in Cycle II, it increased to an average of 90 with 100% completeness. Additionally, students became more active and were able to organize ideas more coherently. Therefore, puzzle media is effective in improving descriptive paragraph writing skills in elementary school students.